The Effect of Indonesian and Hokkien Mobile Learning Application Models - Al-Khowarizmi Al-Khowarizmi; Fauzi Fauzi; Indah Purnama Sari; Ajulio Padly Sembiring (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2020)
Tiongkok is a country with a large population and is in several states. In addition, Tiongkok has a variety of languages. Hokkien is the worldwide language of China and is widely known to many people. This is evidenced by the many China Town markets. In Indonesia there has been a lot of Hokkien language guidance. In almost every elementary school in the city, adding Hokkien language lessons is a must for elementary school students. Even starting from the playgroup has also been taught Hokkien. But still there are children who do not understand because of the different ways of writing by reading Hokkien. In this research, the writer makes an android-based hokkien language learning media which can be utilized by users with mobile technology, designed learning media adapted to the curriculum in elementary schools with 5 subject matter. From the results of testing designed learning media can help make it easier for students to better understand hokkien language.